Penyuluhan Hukum Pemahaman Hak Cipta Terhadap Pelanggaran Karya Cipta Bagi Mahasiswa - Oktaviarni, Firya; Suryahartati, Dwi; Windarto, Windarto; Idris, Isran; Manik, Herlina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Copyright is a protection given to people in the Indonesian homeland as a form of appreciation for the works created. The function of copyright itself is to protect works from individuals who want to plagiarize or imitate these copyrighted works so that others are encouraged to produce ideas and works for the Indonesian nation. And this is protected by the Indonesian Copyright Law and as we know Copyright has various types and one of them is cinematography which is regulated in Article 40 Letter m of the Copyright Law, examples of cinematography. this is like advertising, cartoons, and documentaries. The development of technology and the internet makes it easier for many things to be practical but there are increasing problems that arise in the field of Copyright in the field of film and music works. Piracy or imitation is an act committed by irresponsible people who wish to profit from the work of others without their permission or knowledge. The imperfect maturity of teenagers' thinking brings a negative influence on bad information through social media. As we know, social media is a place for teenagers to express their freedom of expression, be it in the form of pictures or messages that are sometimes misleading. Some of the positive and negative impacts resulting from the use of social media